Correlation of neurochemical and imaging markers in migraine: PACAP38 and DTI measures. (18th September 2018) - Veréb, Dániel; Szabó, Nikoletta; Tuka, Bernadett; Tajti, János; Király, András; Faragó, Péter; Kocsis, Krisztián; Tóth, Eszter; Kincses, Bálint; Bagoly, Teréz; Helyes, Zsuzsanna; Vécsei, László; et al.
Abstract : Objective: To examine whether interictal plasma pituitary adenylate cyclase-activating peptide 38-like immunoreactivity (PACAP38-LI) shows correlation with the microstructural integrity of the white matter in migraine. Methods: Interictal plasma PACAP38-LI was measured by radioimmunoassay in 26 patients with migraine (24 women) who underwent diffusion tensor imaging afterward using a 1.5-tesla magnetic resonance scanner. Data were analyzed using tract-based spatial statistics included in FMRIB's Software Library. Results: Interictal plasma PACAP38-LI showed significant correlation with mean diffusivity ( p < 0.0179) mostly in the bilateral occipital white matter spreading into parietal and temporal white matter. Axial and radial diffusivity showed positive correlation with interictal PACAP38-LI ( p < 0.0432 and p < 0.0418, respectively) in the left optic radiation and left posterior corpus callosum. Fractional anisotropy did not correlate significantly with PACAP38-LI. With disease duration as a nuisance regressor in the model, PACAP38-LI correlated with axial and mean diffusivity in the left thalamus ( p < 0.01). Conclusion: We report a link between PACAP38, a pathobiologically important neurochemical biomarker, and imaging markers of the disease that may bolster further research into the role of PACAP38 in migraine.